Study of a high order family: Local convergence and dynamics - Amorós, Cristina; Argyros, Ioannis K; González-Crespo, Rubén; Magreñán, Á. Alberto; Orcos, Lara; Sarría, Íñigo (Mathematics, 2019)
The study of the dynamics and the analysis of local convergence of an iterative method, when approximating a locally unique solution of a nonlinear equation, is presented in this article. We obtain convergence using a center-Lipschitz condition where the ball radii are greater than previous studies. We investigate the dynamics of the method. To validate the theoretical results obtained, a real-world application related to chemistry is provided.
Keywords: high order; sixteenth order convergence method; local convergence; dynamics; Scopus